Cultural Dimensions in Television Advertising: A Semiotic Study - Al-Rawi, Bushra Jameel; Al-Mamoori, Dhulfiqar Fadhil Salman (ALBAHITH ALALAMI, 2025)
Objectives: This research aimed to highlight the semiotic approach in analyzing television advertising, to uncover the hidden and indirect meanings behind the apparent message of the advertisement "Zain Ya Baghdad" through semiotic analysis. It also incorporated cultural analysis using Hofstede's cultural dimensions, to reveal the relationship between text and image and understand the factors influencing the semiotics of the image, given that it contains signs, symbols, rules, and meanings rooted in the prevailing social and intellectual conditions of society.Methodology: The research stages were conducted by deconstructing the advertisement scenes into individual shots and analyzing them, then reconstructing them to uncover hidden aspects, based on the semiotic analysis approach.Results: The results showed the dominance of the cultural dimension in the content of the advertisement, which was not merely a direct commercial promotion but was laden with cultural and heritage meanings. Elements of Iraqi identity such as music, locations, characters, language, and clothing were employed to deliver an emotional message about Baghdad. Visual and iconic symbols served the cultural meaning by incorporating traditional professions like coppersmithing and calligraphy, and famous locations such as Al-Mutanabbi Street and traditional cafés, enabling the advertisement to present Baghdad as a unifying cultural and emotional symbol. Additionally, the analysis revealed inconsistencies with some of Hofstede's indicators for Iraq, showing clear discrepancies between the global Hofstede classification and the culture reflected in the advertisement.Conclusions: Television advertising is no longer merely a promotional tool but has become a medium for constructing cultural symbols and reinforcing collective identity. The study reveals that cultural values in Iraqi society, as represented in the advertisement, partially differ from Hofstede's indicators, reflecting unique local cultural characteristics.